-2(-5-7q)=

Simple and best practice solution for -2(-5-7q)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(-5-7q)= equation:


Simplifying
-2(-5 + -7q) = 0
(-5 * -2 + -7q * -2) = 0
(10 + 14q) = 0

Solving
10 + 14q = 0

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '-10' to each side of the equation.
10 + -10 + 14q = 0 + -10

Combine like terms: 10 + -10 = 0
0 + 14q = 0 + -10
14q = 0 + -10

Combine like terms: 0 + -10 = -10
14q = -10

Divide each side by '14'.
q = -0.7142857143

Simplifying
q = -0.7142857143

See similar equations:

| 3(y+7)=24 | | 2y-14=x | | -2(-2x-3)=(-2) | | -6B=-420 | | 6a-9=50 | | -8+a=27 | | 4u-12=56 | | 12=-x+9-5x | | 5x-6+x^2=2 | | 9t^2=3t | | (2w-1)(2w-1)x^2=21 | | -4n-2=3n+5 | | 9j+4=4j+14 | | 5/7ab-35b | | 3x-6=15x+18 | | 4y+5=y+9 | | 0.5x+10=1.8x+25.6 | | (4m+1)(m+11)=0 | | m-1/6-4m+5/6= | | ln10/9 | | 162x^4y^2+32y^2= | | x(x)+6x=7 | | (9x-8)(5x+9)= | | 5/8y+7/8y+1/8y= | | 1134=6(x+16) | | x(x)-12x=-8 | | 4m+7(3m-8)= | | (2+x)(x)(3)=240 | | -.3p-2.1=-3.6 | | 3x(x)+14x-5=0 | | (4200*2/3)6 | | -2x+7(0)=11 |

Equations solver categories